Pengaruh Sertifikasi Halal dan Pemasaran Syariah Terhadap Peningkatan Penjualan Usaha Mikro Kecil di Kabupaten Jepara - Kharimatun Nikmah, Nanda; Aan Zainul Anwar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of halal certification and sharia marketing on increase sales of micro and small businesses in Jepara district. This study is a descriptive quantitative study, primary data obtained by distributing questionnaires via google form which is measured by a likert scale. The population in this study was 2,283, it is known that the number of samples using the slovin formula with the purposive sampling method was 97 business actors who already had halal certification, after that a multiple linear regression analysis was conducted using SPSS 22 software. The results of the study simultaneously showed a significant positive effect on increasing sales. Then, the partial results showed that halal certification was significantly positive on increasing sales, and sharia marketing was significantly positive on increasing sales.